2016
DOI: 10.1155/2016/1656182
|View full text |Cite
|
Sign up to set email alerts
|

Severe Ketoacidosis Associated with Canagliflozin (Invokana): A Safety Concern

Abstract: Canagliflozin (Invokana) is a selective sodium glucose cotransporter-2 (SGLT-2) inhibitor that was first introduced in 2013 for the treatment of type 2 diabetes mellitus (DM). Though not FDA approved yet, its use in type 1 DM has been justified by the fact that its mechanism of action is independent of insulin secretion or action. However, some serious side effects, including severe anion gap metabolic acidosis and euglycemic diabetic ketoacidosis (DKA), have been reported. Prompt identification of the causal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 9 publications
0
24
0
Order By: Relevance
“…We retrieved a total of 105 episodes of DKA in patients receiving SGLT2i from May 2014 to April 2017 . Demographic characteristics, type of diabetes and type of SGLT2i are reported in Table .…”
Section: Review Of the Literaturementioning
confidence: 99%
“…We retrieved a total of 105 episodes of DKA in patients receiving SGLT2i from May 2014 to April 2017 . Demographic characteristics, type of diabetes and type of SGLT2i are reported in Table .…”
Section: Review Of the Literaturementioning
confidence: 99%
“…SGLT 2 inhibitor is the newest class of anti diabetic medications approved recently by the US food and drug agency to be used in conjunction with diet and exercise for treatment of type 2 diabetes mellitus [1]. Canagliflozin, dapagliflozin and empaglifilozin are the SGLT-2 inhibitors currently approved by the FDA [2].…”
Section: Discussionmentioning
confidence: 99%
“…The most common adverse reactions associated with canagliflozin are genital mycotic infections, urinary tract infections, osmotic diuresis, and reduced intravascular volume [1] but FDA revised the labels more recently to include warnings and precautions about the risks of ketoacidosis with SGLT 2 inhibitors [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some cases of DKA in T2DM patients were euglycemic 5860. Other cases of DKA were associated with off-label use of SGLT2 inhibitors in patients with type 1 diabetes mellitus 58,61,62. SGLT2 inhibitor clinical trials reported low frequencies of DKA in T2DM: canagliflozin events by treatment group were 0.07% (4/5,337), 0.11% (6/5,350), and 0.03% (2/6,909) for 100 mg, 300 mg, and comparator, respectively;63 dapagliflozin events were <0.1% in >18,000 patients (no further details stated);64 and DKA events with empagliflozin by treatment group were 2 events for 10 mg and 1 event for 25 mg, vs 5 events for placebo (N>13,000 T2DM patients; treatment group sizes not stated) 64.…”
Section: Summary Of Mechanisms Efficacy and Safetymentioning
confidence: 99%